High Energy Efficiency Retrofits in Portugal. (December 2015) - Rodrigues, Fernanda; Parada, Marlene; Vicente, Romeu; Oliveira, Rui; Alves, Ana
Abstract: The current European concerns for new and existent buildings are currently being tackled as "Near-Zero Energy Buildings" in the scope of the Energy Performance of Building Directive (EPBD, 2010). Buildings' retrofit is taken as a valuable and sustainable opportunity for reducing energy consumption and greenhouse gases (GHG) emissions in order to accomplish the nZEB requirements. In Portugal, the complexity associated to current renovation processes carried out within urban areas usually leads to unsustainable and inefficient energy strategies, being crucial therefore, to raise awareness for the development of more reliable retrofit solutions to invert this trend. The high energy performance of buildings achieved by complying with the requirements of Passive House standard is subjacent in EPBD. Energy retrofit based on passive solutions will contribute to the sustainability of urban centres on different levels: environment, economic and social. Hence, this study aims to contribute for the exploitation of this particular matter by assessing the favourable applicability of EnerPHit standard in existing buildings, taking for case study a 19th Century stone masonry building, located in Oporto, in Portugal, which was subjected to a deep retrofit process.